Hsiaotycoris tuberculatus, a new genus and species of Harpactorinae (Heteroptera: Reduviidae) from China - Lü, Zhaozhi; Zhao, Ping; Cai, Wanzhi (Zootaxa, 2006)
Hsiaotycoris tuberculatus Lü, Zhao & Cai, gen. & sp. nov. of the harpactocorine tribe Dicrotelini from China is described and illustrated. A key and diagnostic characters are provided to distinguish the new genus from morphologically related genera.